2019
DOI: 10.1007/s12571-019-00923-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between forest cover and diet quality: a case study of rural southern Malawi

Abstract: The importance of forests in supporting the well-being of poor rural communities cannot be overstated, not only for improving food security but also for biodiversity conservation. For many people living in developing regions of the world, forests provide healthy and nutrient-dense foods which can improve overall diet quality and act as a safety net during times of hardship. Forests can also provide a source of income and facilitate certain agricultural practices, potentially allowing for poverty alleviation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 71 publications
(149 reference statements)
0
8
0
Order By: Relevance
“…Vira et al (2015) has elucidated that forest and tree-based systems contribute to the nutritional security of communities and provide the needed micronutrients particularly for children and women. The study by Ickowitz et al (2016) found that people living close to forests in Indonesia consumed more nutritious foods and in Malawi households located in areas with a high percentage of forest cover had significantly improved vitamin A adequacy (Hall et al, 2019). In Meghalaya, there are unique systems of matriliny and matrilocality where women are custodians of the intergenerational property including land.…”
Section: Discussionmentioning
confidence: 99%
“…Vira et al (2015) has elucidated that forest and tree-based systems contribute to the nutritional security of communities and provide the needed micronutrients particularly for children and women. The study by Ickowitz et al (2016) found that people living close to forests in Indonesia consumed more nutritious foods and in Malawi households located in areas with a high percentage of forest cover had significantly improved vitamin A adequacy (Hall et al, 2019). In Meghalaya, there are unique systems of matriliny and matrilocality where women are custodians of the intergenerational property including land.…”
Section: Discussionmentioning
confidence: 99%
“…Though proximity to forested areas was not considered in our study design, Tata's findings are suggestive that similar factors could be at play in our results. Analogous patterns between dietary diversity, micronutrient deficiencies such as IDA, and proximity to forested areas have been observed world-wide, especially in tropical regions [7,[18][19][20].…”
Section: Location and Hemoglobinmentioning
confidence: 75%
“…They have supplemented the diet of rural families by providing essential micronutrients, antioxidants, polyphenols, and health benefits, especially for mothers and children. They also serve as an alternative for income (cash and barter), especially during times of food scarcity and economic hardship [16,78,[473][474][475][476][477], as such they play an important role in reducing the vulnerability of rural households to hunger and poverty in southern Africa [472]. In Zimbabwe, indigenous fruit trees can reduce this vulnerability by 33% during critical periods in the cropping season [473], also providing a coping strategy for farmers in Zambia and Malawi during periods of drought.…”
Section: The State Of Natural Resources and Their Governance And Mana...mentioning
confidence: 99%